THE EFFECT OF COOPERATIVE PSYCHOLOGICAL CLIMATE ON PUBLIC SERVICE PERFORMANCE: THE MEDIATING ROLE OF HARMONIOUS PASSION AND ORGANIZATIONAL COMMITMENT - Fitri Wulandari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study was intended to analyze the role of the cooperative psychological climate in improving public service performance mediated by harmonious passion and organizational commitment. Using probability sampling, cluster sampling was used to select the samples of 165 employees who work in the public sectors. The results of the path analysis employing software IBM SPSS statistics 23 show a significant positive effect of cooperative psychological climate on harmonious passion and organizational commitment. However, there is no significant effect of the cooperative psychological climate on public service performance. The results also describe that harmonious passion has no significant effect on public service performance. Organizational commitment has a significant negative effect on public service performance. Organizational commitment fully mediate the effect of the cooperative psychological climate on public service performance. However, that is not the case for harmonious passion, which does not mediate the effect. The upshot of this study is that organizations are expected to continue to finalize the concepts of workplace competence, autonomy, and engagement in creating a cooperative climate in the workplace to increase organizational commitment and harmonious passion.